Clinical Outcome of Pneumatic Dilatation in Patients with Achalasia Cardia: A Single-Center Prospective Study - Shejal, Amit Hanmant; Ramachandran, Thazhath Mavali; Kumar N, Sunil (Journal of Digestive Endoscopy, 2017)
Background and Aim: Pneumatic balloon dilation is one of the most commonly used and effective methods for treating patients with achalasia cardia. This study was performed to assess immediate and long-term response of pneumatic dilatation (PD) in these patients. Materials and Methods: Forty-four achalasia cardia patients, who underwent PD in our center from January 2013 to December 2015, were prospectively studied. Data from these patients were analyzed for clinical improvement in symptoms after dilatation procedure over this period as per Eckardt score. Patients who required repeated procedure and factors influencing remission of symptoms were analyzed. Results: A total of 44 patients underwent PD, among which three lost to follow up. Of the 41 patients, 21 were male (51.22%) and 20 were females (48.78%). Mean age was 38.68 (13–64) years. Median symptom duration before first dilatation was 18 months (2–240). Major symptoms at presentation were dysphagia (n = 41, 100%), regurgitation (n = 38 92.68%), chest pain (n = 31, 75.6%), and weight loss (n = 20, 48.78%). Mean follow-up period was 22.22 months (9–38). Forty (97.56%) patients had immediate clinical improvement after 1 dilatation, of which 38 (92.68%) patients did not require any further treatment. Mean Eckardt score was 6.82 (4–11) at the time of first dilatation which improved to 0.66 during follow-up. Two patients required second dilatation (one 5 months and other 18 months after the first procedure). Conclusion: PD is a safe and effective long-term therapy for achalasia cardia and has a good long-term clinical remission.
Keywords: Achalasia cardia; Eckardt score; pneumatic dilatation